Gender Role Attitudes and Equality at Workplace: A Literature Review - Gunatilaka, P. D. H .D.; Rajapakse, R. P. C. R. (University of Jaffna, 2018)
Gender role attitudes have impacts on the lives of women around the globe irrespective of being employed or not. Women’s increasing participation in the world of work and the revolution in gender knowledge which considered gender as a social construction have attracted the attention of world leaders on gender equality and empowering women. Organisations being social entities, prevailing gender role attitudes in respective cultures result in reproducing gender inequality within organizations with the use of organisational policies, practices and relations. Literature highlights that irrespective of the major efforts made by different institutions such as the United Nations, prevalence of gender role attitudes and the presence of gender inequality in organisations are equally significant in the global North as well as in the global South
Keywords: Women; Gender role attitudes; Gender inequality; Organisational factors